2019
DOI: 10.1038/s41598-018-37031-6
|View full text |Cite
|
Sign up to set email alerts
|

Superficial sedimentary stocks and sources of carbon and nitrogen in coastal vegetated assemblages along a flow gradient

Abstract: Coastal vegetated ecosystems are major organic carbon (OC) and total nitrogen (TN) sinks, but the mechanisms that regulate their spatial variability need to be better understood. Here we assessed how superficial sedimentary OC and TN within intertidal vegetated assemblages (saltmarsh and seagrass) vary along a flow gradient, which is a major driver of sediment grain size, and thus of organic matter (OM) content. A significant relationship between flow current velocity and OC and TN stocks in the seagrass was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 66 publications
4
31
1
Order By: Relevance
“…In other words, meadows with lower water motion exhibited higher sediment OC stocks, likely due to enhanced particle deposition and reduced rates of erosion and resuspension in these calmer hydrodynamic environments. Our results agree with previous field studies examining the role of hydrodynamics on seagrass meadow carbon storage, where greater sediment carbon content was associated with lower wave heights (Samper‐Villarreal et al ), lower wave exposure (Mazarrasa et al ), and lower current velocities (Santos et al ). Carbon stocks have also been shown to be significantly higher in inner fjords compared to outer fjords and open coasts (Kindeberg et al ), which aligns with our finding that more sheltered inner‐coast sites such as Pruth Bay had much higher OC stocks than exposed outer coast sites such as Choked Pass (Table ; Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, meadows with lower water motion exhibited higher sediment OC stocks, likely due to enhanced particle deposition and reduced rates of erosion and resuspension in these calmer hydrodynamic environments. Our results agree with previous field studies examining the role of hydrodynamics on seagrass meadow carbon storage, where greater sediment carbon content was associated with lower wave heights (Samper‐Villarreal et al ), lower wave exposure (Mazarrasa et al ), and lower current velocities (Santos et al ). Carbon stocks have also been shown to be significantly higher in inner fjords compared to outer fjords and open coasts (Kindeberg et al ), which aligns with our finding that more sheltered inner‐coast sites such as Pruth Bay had much higher OC stocks than exposed outer coast sites such as Choked Pass (Table ; Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The scarcity of data on the spatial heterogeneity in carbon stocks and accumulation rates creates challenges for scaling up carbon estimates and incorporating blue carbon into such climate policies (Lavery et al ; Oreska et al ; Mazarrasa et al ). Furthermore, the mechanisms that regulate spatial variability across different scales are only beginning to be understood (Samper‐Villarreal et al ; Kindeberg et al ; Mazarrasa et al ; Santos et al ).…”
mentioning
confidence: 99%
“…Some tropical seagrass species can, for instance, be a direct source of inorganic carbon to the sediment by formation of aragonite crystals in the leaves (Enríquez & Schubert, ); this has, however, not been seen in any temperate seagrass species. The C: N ratio was similar to previous studies on the Swedish west coast (Dahl, Deyanova, Gütschow, et al, ; Pihl et al, ) and elsewhere in the region (Kindeberg et al, ), with low nitrogen content in relation to organic carbon levels, which is also commonly found in other seagrass areas (Gullström et al, ; Santos et al, ). The highest nitrogen content was found in the carbon‐rich, sheltered site of Getevik, as the nitrogen content is known to positively correlate to both carbon‐ and silt‐clay content (Kindeberg et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Variability in seagrass sedimentary C org stocks has been described at a range of spatial scales: from cm and meters, at the seagrass patch and meadow scale [18][19][20] to bioregions and latitudinal scales 7,9 . Studies at small scales (up to ~1′s km) have shown how sedimentary C org can be spatially distributed inside seagrass meadows 18,20,21 . However, in studies at higher spatial scales (~100′s to ~1000′s km), comparisons and estimates are usually made based on a relatively low number of sediment cores from each site [22][23][24] , therefore, not accounting for the potential spatial variability in seagrass sedimentary C org stocks among meadows in the same area.…”
mentioning
confidence: 99%